Determinants of vitamin D supplementation prescription in nursing homes: a survey among general practitioners. Issue 3 (March 2016) - Buckinx, F.; Reginster, J.; Cavalier, E.; Petermans, J.; Ricour, C.; Dardenne, C.; Bruyère, O.
Abstract Summary A total of 119 GPs participated to a survey aimed to assess the profile and determinants of vitamin D supplementation prescription in nursing homes. Among the respondent GPs, 65 (54.6 %) systematically prescribe vitamin D to their institutionalized patients and the 54 (45.4 %) others prescribe only sometimes. Introduction The aim of this study is to assess the profile and determinants of vitamin D supplementation prescription in nursing homes. Methods General practitioners (GPs) having at least one patient in a nursing home in Liège, Belgium, were asked to complete the survey. Results A total of 119 GPs participated in the survey. Among the respondent GPs, 65 (54.6 %) systematically prescribe vitamin D to their institutionalized patients and the 54 (45.4 %) others prescribe only sometimes. The main reasons for prescribing vitamin D cited by GPs who do so systematically are as follows: because they believe nursing home residents are mostly deficient in vitamin D status (92.1 %), because they believe that vitamin D supplementation prevents osteoporotic fractures (77.8 %), and because vitamin D supplementation is recommended by various scientific societies (38.1 %). GPs who only prescribe vitamin D supplementation in some patients mainly do so following a diagnosis of osteoporosis (82.4 %), on the basis the 25(OH)D level (78.4 %), in the case of history of fracture (54.9 %) or after a recent fracture (43.4 %). Surprisingly, 16 physicians (31.4 %) only prescribe vitamin D when they think of it. Interestingly, while 40.7 % of GPs always prescribe the same dose of vitamin D, the remaining 59.3 % prescribe a dose that will mainly depend on the results of the 25(OH)D level (94.0 %), the patient's bone health (49.3 %), or history of fracture (43.3 %). Conclusions More than half of GPs systematically prescribe vitamin D to their patients living in nursing homes. The other GPs usually prescribe vitamin D following the result of the vitamin D status or after a diagnosis of osteoporosis.